1997
DOI: 10.1074/jbc.272.38.23585
|View full text |Cite
|
Sign up to set email alerts
|

Urokinase and Tissue-type Plasminogen Activator Are Required for the Mitogenic and Chemotactic Effects of Bovine Fibroblast Growth Factor and Platelet-derived Growth Factor-BB for Vascular Smooth Muscle Cells

Abstract: The present study was undertaken to evaluate in vitro the relative importance of tissue-type plasminogen activator (t-PA) and urokinase-type plasminogen activator (u-PA) in the mitogenic and chemotactic potential of bovine fibroblast growth factor (bFGF) and platelet-derived growth factor (PDGF)-BB for smooth muscle cells (SMC). Aortic SMC were isolated from transgenic mice showing single inactivations of the t-PA, u-PA, plasminogen activator inhibitor-1, or urokinase-type plasminogen activator receptor (u-PAR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 58 publications
4
45
1
Order By: Relevance
“…26,39 Studies on vascular smooth muscle cells produced similar findings that uPA induces proliferation of these cells and may mediate growth factor-induced proliferation. [40][41][42] Our data demonstrated that (1) intact uPA but not the aminoterminal fragment, which lacks the proteolytic domain, stimulated myoblast proliferation; (2) the specific proteolytic inhibitor PAI-1 blocked uPA-mediated myoblast proliferation; (3) the HGFblocking antibody reduced uPA stimulation of myoblast proliferation; and (4) both the PI3K inhibitor LY and the MEK1 inhibitor PD98059 reduced uPA-mediated myoblast proliferation. Taken together, these data indicate that uPA stimulates myoblast proliferation through proteolytic activation of HGF and via signaling through PI3K and MEK1.…”
Section: Org Frommentioning
confidence: 99%
“…26,39 Studies on vascular smooth muscle cells produced similar findings that uPA induces proliferation of these cells and may mediate growth factor-induced proliferation. [40][41][42] Our data demonstrated that (1) intact uPA but not the aminoterminal fragment, which lacks the proteolytic domain, stimulated myoblast proliferation; (2) the specific proteolytic inhibitor PAI-1 blocked uPA-mediated myoblast proliferation; (3) the HGFblocking antibody reduced uPA stimulation of myoblast proliferation; and (4) both the PI3K inhibitor LY and the MEK1 inhibitor PD98059 reduced uPA-mediated myoblast proliferation. Taken together, these data indicate that uPA stimulates myoblast proliferation through proteolytic activation of HGF and via signaling through PI3K and MEK1.…”
Section: Org Frommentioning
confidence: 99%
“…Transforming growth factor-␤ 1 (TGF␤ 1 ) 183,184 Tumor necrosis factor-␣ (TNF␣) 185,161 Thrombin 186 Urokinase plasminogen activator 187,188 Vascular endothelial growth factor (VEGF) 189,190 Extracellular matrix components Collagen I, IV 37 Collagen VIII 191,192 Sphingosine-1 phosphate (S1P) 75,76 formins (mDia1 and mDia2), which act on the plus end in concert with profilin. The formin mDia1 is activated by RhoA, and mDia2 is activated by Cdc42.…”
Section: Pdgf 23mentioning
confidence: 99%
“…Normal human dermal fibroblasts were plated at a density of 10 5 cells/well in six-well culture plates and grown until subconfluence in MEM containing 10% FCS. Cells were quiesced by 24-h incubation in serum-free MEM, followed by incubation in serum-free medium in the presence or absence of SIS3 before the collection of cells for 72 h. Then, the cells were detached from the wells by trypsin treatment and counted using a Coulter counter (Beckman Coulter, Fullerton, CA) (Herbert et al, 1997 3 H]proline} (GE Healthcare) was added to the medium and incubated overnight. Medium was harvested from each well, and the incorporated radioactivity was counted in a liquid scintillation counter (Ziyadeh et al, 1994;Isono et al, 2000).…”
Section: Sis3 Is a Novel Inhibitor Of Smad3 599mentioning
confidence: 99%